A novel non-viral gene vector for hepatocyte-targeting and in situ monitoring of DNA delivery in single cells. Issue 55 (23rd May 2016) - Gao, Yong-Guang; Tang, Quan; Shi, You-Di; Zhang, Ying; Wang, Ruibing; Lu, Zhong-Lin
Abstract : A macrocyclic polyamine lipid bearing both fluorescent naphthalimide and targeting cholic acid moieties, 1, was designed and synthesized as a novel non-viral gene vector. Abstract : A macrocyclic polyamine lipid bearing both fluorescent naphthalimide and targeting cholic acid moieties, 1, was designed and synthesized as a novel non-viral gene vector. Plasmid DNA was completely condensed at 10 μM of1 (N/P = 3.6) in 5 minutes at 37 °C. The process of DNA uptake process by1 in a single cell was clearly investigated through time-dependent fluorescence microscopy assay. Flow cytometry experiments of liposome1 clearly proved its targeting activity toward HepG2 cells. Luciferase gene expression transfected by the DNA complex of1 /DOPE gave a higher transfection efficiency in HepG2, A549, HeLa, U2OS and CCC-HPF-1 cells than by lipofectamine 2000. The present work demonstrated that the designed multifunctional organic molecule is able to fluorescently track the gene delivery process at a single-cell level for the first time. This will greatly aid mechanistic studies of gene transfection and further development of new gene vectors for biomedical applications.